Richard Hayman donation in The Center for Steinbeck Studies, in the Dr. Martin Luther King Jr. Library. - Tim Cech:::Photographer:::::::::::: (San Jose, California, 2023)
A view of the holding shelves for a portion of the Richard Hayman donation in The Center for Steinbeck Studies. Lee Richard Hayman was a former Salinas High School teacher, historian and John Steinbeck scholar and collector. Hayman was also co-founder of the National Steinbeck Center in Salinas.